The effect of organizational conflict management strategies in the organizational climate Analytical study in the General Company for the transmission of electric power one of the formations of the Ministry of Electricity in Baghdad - Ammar Jabbar Kadhim Alaboody (Journal of Madenat Alelem University College, 2021)
The research aims to identify the effect of organizational conflict management strategies on the organizational climate, the research was applied at the General Electricity Transmission Company, one of the formations of the Ministry of Electricity in Iraq, Integrated theoretical and comprehensive aspects of the research variables were presented. and using a questionnaire containing (35) questions covering all aspects of the research, the researcher used the descriptive analytical method in order to identify the level of impact relationship between the research variables, where (66) questionnaires were subjected to statistical analysis, The researcher has used the scientific statistical methods symbolized by (SPSS: V-24) and the program (Excel: V-2013) in order to analyze the data obtained through the questionnaire and some personal interviews through scientific statistical methods. The results of the research confirmed the existence of a significant effect relationship for organizational conflict management strategies in the organizational climate. The research recommended the necessity of making the best use of organizational conflict management strategies in creating and creating an appropriate and suitable organizational climate for work in the organization.